The Effect of Paper Craft Activities on Children's Creativity in Group B: A Pre-Experimental Study with a Single Group Pretest and Posttest Design - Winda Ananta Akmal; Durrotunnisa Durrotunnisa; Fitriana Fitriana; Shofiyanti Nur Zuama (Journal of Educational Sciences, 2026)
Creativity is a crucial skill for early childhood in generating innovative ideas and original works. This study aims to analyze the effect of papercraft activities on the creativity of children in Group B at Harapan Mulia Kindergarten in Palu City. The research method used a quantitative approach with a One-Group Pretest-Posttest Pre-Experimental design on a sample of 15 children. Data were collected through observation, documentation, and interviews focusing on the aspects of originality, elaboration, and fluency. The results showed a significant increase in children's creativity after the intervention. Before the intervention, most children were in the Not Yet Developed and Beginning to Develop categories, but after the application of papercraft, the children reached the Developing as Expected and Developing Very Well categories. Statistical analysis proved that the research hypothesis was accepted, which showed that paper craft activities were effective in significantly increasing the creativity of early childhood.